2022
DOI: 10.1038/s41420-022-01048-8
|View full text |Cite|
|
Sign up to set email alerts
|

BMP9 reduces age-related bone loss in mice by inhibiting osteoblast senescence through Smad1-Stat1-P21 axis

Abstract: Age-related osteoporosis is characterized by the accumulation of senescent osteoblastic cells in bone microenvironment and significantly reduced osteogenic differentiation. Clearing of the senescent cells is helpful to improve bone formation in aged mice. Bone morphogenetic protein 9 (BMP9), a multifunctional protein produced and secreted by liver, was reported to improve osteoporosis caused by estrogen withdrawal. However, the mechanism of BMP9 has not been fully elucidated, and its effect on senile osteoporo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Research has shown that Bmp9 treatment inhibits osteoblast senescence through activating Smad1, which suppresses the transcriptional activity of Stat1, thereby inhibits P21 expression and SASPs production. 29 Sun Y et al showed that 82% (82/100) of pancreatic adenocarcinoma cases expressed Stat1 protein, whereas 72% (72/100) of PA cases expressed p21 protein. The expression of these 2 proteins was positively correlated (co-expressed in tumor cells), whereas the loss of expression of Stat1 and p21 proteins was associated with tumor dedifferentiation, advanced clinical stages, and LN metastasis of pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that Bmp9 treatment inhibits osteoblast senescence through activating Smad1, which suppresses the transcriptional activity of Stat1, thereby inhibits P21 expression and SASPs production. 29 Sun Y et al showed that 82% (82/100) of pancreatic adenocarcinoma cases expressed Stat1 protein, whereas 72% (72/100) of PA cases expressed p21 protein. The expression of these 2 proteins was positively correlated (co-expressed in tumor cells), whereas the loss of expression of Stat1 and p21 proteins was associated with tumor dedifferentiation, advanced clinical stages, and LN metastasis of pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in the number and function of BMSCs are an important cause of senile osteoporosis [ 80 , 81 , 82 ]. The proportion of senescent BMSCs in the skeletal microenvironment increases with age, thereby leading to a decrease in the osteogenic capacity of osteoblasts [ 81 , 83 ]. Notably, only a small fraction of cells undergo senescence even at advanced ages.…”
Section: Effect Of Bmsc Aging On Osteoporosismentioning
confidence: 99%
“…proved that overexpression of BMP9 led to not only elevated BMP9 levels in the liver and serum but also suppressed bone resorption activity, improved cortical and trabecular volumetric BMD, and ameliorated bone strength in an ovariectomy mouse model ( 21 , 60 ). BMP9 increased bone mass in aged mice by preventing osteoblast senescence and stimulating osteoblast differentiation, improved bone biomechanical properties, and ameliorated the bone microenvironment ( 61 ). Aside from directly influencing bone resorption and bone formation, BMP9 upregulated the endogenous expression of RUNX3 in mesenchymal stem cells ( 62 ), which are undifferentiated stem cells with the potential to differentiate into multiple lineages, including osteoblasts ( 63 ).…”
Section: Hepatokines: From Liver To Bonementioning
confidence: 99%